Using Underwater Acoustic Data To Predict the Distribution of Demersal Fish in Western Australia - Landero Figueroa, Marcela Montserrat (Curtin University, 2018)
This study focuses on helping in the assessment of demersal reef fish distribution in the coast of Western Australia. Models of potential distribution of demersal species were created using biological data form baited remote underwater stereo-videos (stereo-BRUVS) and benthic surrogates based on acoustic data. The possibility of combining optic and acoustic methods to produce a more holistic assessment of demersal fish distribution was also explored.